Financial Management Behavior with Locus of Control as an Intervening Variable: Impact of of Financial Knowledge and Income Level - Sudarmawanti, Erna; Mar'ati, Fudji Sri; Ningrum, Diah Kusuma (Ekonomis: Journal of Economics and Business, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are business sectors that offer a range of goods and services and play a significant role in developing new industries as a solution to the unemployment issue. MSMEs have a huge potential to boost local economic activity and provide the majority of people with a source of income, which would improve welfare. MSMEs are still growing, but it is not slow and stagnant growth because of issues including capital constraints, a lack of utilization of information and technology, and poor financial literacy in managing company finances. The primary data for this study came from questionnaire surveys that were conducted directly. The results of the study allow for several inferences: The degree of income and financial literacy has a significant impact on where control is placed. The way people handle their money has a huge bearing on their financial knowledge. The majority of the time, people's financial management is unrelated to their degree of income. The behavior of financial management is significantly influenced by the locus of control. Financial knowledge has a significant impact on financial management behavior through the locus of control. The placement of control is substantially influenced by income and financial literacy levels. The way people handle their money has a huge bearing on their financial knowledge. The way people manage their finances is mostly independent of their income level. The behavior of financial management is significantly influenced by the locus of control. Financial knowledge has a significant impact on financial management behavior through the locus of control.